2017
DOI: 10.18632/oncotarget.18360
|View full text |Cite
|
Sign up to set email alerts
|

Cblb-deficient T cells are less susceptible to PD-L1-mediated inhibition

Abstract: Modulation of the immune system for the treatment of primary and metastatic tumors has been a goal of cancer research for many years. The E3 ubiquitin ligase Cbl-b has been established as an intracellular checkpoint that limits T cell activation, critically contributing to the maintenance of self-tolerance. Furthermore, it has been shown that Cblb deficiency enhances T cell effector functions towards tumors. Blockade of the immune checkpoints CTLA-4 and PD-1/PD-L1 has recently emerged as a promising strategy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Early studies demonstrated that Cbl-b can be re-expressed in response to CTLA-4 signaling, and CTLA-4 deficient T cells display reduced Cbl-b expression (153). Recent studies suggest that T cells deficient in Cbl-b are less susceptible to PD-1 inhibitory signaling in vitro (154, 155). These findings are consistent with a study suggesting that SHP-1, which plays an important role in downstream PD-1 and CTLA-4 signaling pathway, controls Cbl-b activity through direct phosphorylation (156).…”
Section: Reported Cases Of Treg Resistancementioning
confidence: 99%
“…Early studies demonstrated that Cbl-b can be re-expressed in response to CTLA-4 signaling, and CTLA-4 deficient T cells display reduced Cbl-b expression (153). Recent studies suggest that T cells deficient in Cbl-b are less susceptible to PD-1 inhibitory signaling in vitro (154, 155). These findings are consistent with a study suggesting that SHP-1, which plays an important role in downstream PD-1 and CTLA-4 signaling pathway, controls Cbl-b activity through direct phosphorylation (156).…”
Section: Reported Cases Of Treg Resistancementioning
confidence: 99%
“…CD28 activation lowers Cbl-b amounts whereas CTLA4 is important for its expression (Li et al 2004). Interestingly, anti-tumor responses in Cbl-b -/mice are more responsive to CTLA4, but not PD1, blockade (Peer et al 2017). In addition, checkpoint inhibtors lead to the upregulation of different classes of T cells against tumors, i.e.…”
Section: How Do Checkpoint Inhibitors Mediate Antitumor Effects?mentioning
confidence: 99%
“…Cblb -/mice also reject transplanted tumors. The rejection of spontaneous tumors or transplanted tumors is mediated by CD8 + T cells [85][86][87]. Interestingly, Cblb -/-CD8 + T cells are resistant to suppression by CD4 + CD25 + Tregs, TGF-β, or PD-L1 [84,85,87].…”
Section: 3b Cbl-b In Cd8 + T Cell Responses In Tumors-cd8mentioning
confidence: 99%
“…The rejection of spontaneous tumors or transplanted tumors is mediated by CD8 + T cells [85][86][87]. Interestingly, Cblb -/-CD8 + T cells are resistant to suppression by CD4 + CD25 + Tregs, TGF-β, or PD-L1 [84,85,87]. Taken together, these studies indicate that inhibition of Cbl-b by small molecule inhibitors or Cblb siRNA may represent an effective strategy to treat patients with tumors in combination with the current immune check-point blockers such anti-PD-1 or anti-PD-L1.…”
Section: 3b Cbl-b In Cd8 + T Cell Responses In Tumors-cd8mentioning
confidence: 99%